PHYSICAL PROPERTIES OF ROCKS OF THE SOUTH-BUKANTAUSKAYA AND NORTHERN - BUKANTAUSKAYA STRUCTURAL-FORMATION SUBZONE - Yusupov Rustam Yunusovich., Khaidarov Botir Khaidarovich., Yusupov Valijon Rustamovich., (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article examines the physical properties of rocks and ores of the North Bukantau structural-formational subzone of the Bukantau mountains to use the information obtained in geophysical prospecting and exploration of ore deposits. In the Central Bukantau subzone, the Late Proterozoic meta-hyperbasic intrusive complex is conditionally distinguished, which is characteristic inclusive of the entire zone of the Bukantau deep fault. It is represented by foliated serpentinite, listvenite and products of their further transformation - birbirat, which are located in the axial part of the deep fault zone, in the form of small bodies, among the tectonic mixture. South Bukantau structural-formational subzone. In this subzone, the most ancient rocks are represented by formations of the Cholcharatau Formation of the Upper Proterozoic. This is a volcanic-sedimentary intensely metamorphosed stratum, consisting of gabbro-diabases, diabases and their tuffs, transformed into amphibolites, amphibole and various crystalline schists, with an apparent thickness of more than 400 m. the position of this area in the marginal resonance-tectanic system of the Kuramino-Fergana median massif. The Yuzhno-Bukantauskaya is built more complexly. Terrigenous deposits of various formational composition, carbonate rocks are developed here. Sedimentary formations are interrupted by numerous felsic intrusions, both exposed on the day surface and not reaching the level of the erosional cut.